His to protect - Cooper, Sharon C. (Harlequin romantic suspense, 2021)
"When Connie Shaw witnesses a bank robbery gone horribly wrong, security specialist Trace Halstead makes himself her personal protection detail. Days and nights together make it impossible for Connie and Trace to resist the attraction burning between them. But Connie doesn't know which she fears more ... the threat from the man who wants to end her life or the love of the man trying to save it?"--Back cover.